Student Management Based On Interests And Talents: An Effective Efforts To Improve Academic And Non-Academic Achievement In Madrasah - Navisatul Qolbiyah, Ema; Nur 'Azah (Jurnal Manajemen Pendidikan Islam Darussalam, 2025)
This study aims to describe student management based on interests and talents and its role in improving academic and non-academic achievement at MTsN 1 Jombang. The background of the study stems from the need for student governance that is not only oriented towards academic achievement, but also the development of talents and interests. This study uses a descriptive qualitative approach with data collection techniques in the form of interviews, observation, and documentation. Informants include the principal, vice principal for curriculum and student affairs, subject teachers, extracurricular supervisors, and students. Furthermore, the data were analyzed inductively using interactive analysis techniques from Milles and Huberman which include data reduction, data presentation, and drawing conclusions. The results show that student management at MTsN 1 Jombang includes structured planning, organizing, implementing, and evaluating stages. Strategies for improving achievement include fostering superior classes, academic competition training, and developing extracurricular activities based on interests and talents. The conclusion of this study shows that good student management contributes significantly to improving overall achievement. Recommendations are directed to the madrasah to strengthen the coaching system and expand support facilities in developing student potential.